(untitled) - Breitmaier, E. (Chichester, West Sussex, England, 2002)
This text provides the graduate student with a systematic guide to unravelling structural information from the NMR spectra of unknown synthetic and natural compounds. A brief introduction gives an overview of the basic principles and elementary instrumental methods of NMR. This is followed by instructional strategy and tactical advice on how to translate spectra into meaningful structural information. The book provides the student with 55 sets of spectra of graduated complexity.
Hoá học các hợp chất tự nhiên,Kỹ thuật hóa học hữu cơ trong phòng thí nghiệm
Keywords: Organic compounds,Hợp chất hữu cơ; Structure,Cấu trúc